Al-Madāris al-Islāmiyyah al-Tābi‘ah li Wazārah al-Shu’ūn al-Dīniyyah ka Madāris Namūzajiyyah 1946-1987 - Husni Rahim (Studia Islamika, 1997)
When the Dutch colonial period, religious education are taken care of by the two departments, namely the Department van Onderwijst en Eeredinst to religious instruction in public schools and the Department Binnenlandsche Zaken van for teaching religion in Islamic institutions, then the Indonesian independence, the two are taken care of the Department of Islamic teaching religion. The governing must have different properties. Understanding the maintenance of the colonial period was more focused on observing, supervising, and maintaining religious education so as not to harm the interests of the colonial government. Being during the Indonesian independence, the maintenance is manifested in the form of foster, assist, and promote (organization) religious education.DOI: 10.15408/sdi.v4i2.783